X+5(-x+6)=7(9-x)

Simple and best practice solution for X+5(-x+6)=7(9-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+5(-x+6)=7(9-x) equation:



X+5(-X+6)=7(9-X)
We move all terms to the left:
X+5(-X+6)-(7(9-X))=0
We add all the numbers together, and all the variables
X+5(-1X+6)-(7(-1X+9))=0
We multiply parentheses
X-5X-(7(-1X+9))+30=0
We calculate terms in parentheses: -(7(-1X+9)), so:
7(-1X+9)
We multiply parentheses
-7X+63
Back to the equation:
-(-7X+63)
We add all the numbers together, and all the variables
-4X-(-7X+63)+30=0
We get rid of parentheses
-4X+7X-63+30=0
We add all the numbers together, and all the variables
3X-33=0
We move all terms containing X to the left, all other terms to the right
3X=33
X=33/3
X=11

See similar equations:

| -2=4-2x/3 | | 2(x-3)+3x=4x-6+x | | –3=–11y | | (-9/5)=x/45 | | 1/3x48+80=1/2x48+120 | | 15=50-2.5(q) | | 3x+(-x-6)=56 | | x+3/4=x-3/5 | | 3x/4-x/2=9 | | 5/a=9/12 | | X+7x=5 | | -3(x-2)=4(2x-4) | | 2x+23=6×-5 | | 3x/4-2=x/2+2 | | g(-2)=5(-2)+3 | | g(5)=5(5)+3 | | -98=7(7v-7) | | –6j=–7j+6 | | h(1)=1+5 | | h(0)=0+5 | | (5x/2)-5=5 | | h(-2)=-2+5 | | 15(x+4)-2(x-2)=5(x-2)+7(x-2) | | h(4)=4(4)-3 | | h(3)=4(3)-3 | | 15​(z+4​)-2​(z-2​)=5​(z-2​)+7​(z-2​) | | 5(7-8n)=155 | | h(2)=4(2)-3 | | h(0)=4(0)-3 | | h(-1)=4(-1)-3 | | 15x+8=4x8 | | f(4)=-5(4)+4 |

Equations solver categories